2017
DOI: 10.1371/journal.pone.0177209
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of mouthparts and feeding performance of Pyrrhocoris sibiricus Kuschakevich with remarks on the specialization of sensilla and stylets for seed feeding

Abstract: Mouthpart structure and feeding behavior in the temperate firebug, Pyrrhocoris sibiricus Kuschakevich, an important pest that feeds on seeds of leguminous and gramineous plants, are described for the first time. Mouthparts were observed using scanning electron microscopy to examine the external morphology, distribution and abundance of sensilla on mouthparts. Feeding performance by adults on both seeds and shoots were observed using a binocular microscope. The four-segmented labium contains 3 types of sensilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(68 citation statements)
references
References 47 publications
8
50
0
Order By: Relevance
“…There were distinct differences in total length of the labium among the four largid bug species observed (longest in Macrocheraia grandis (Lohitini: 19,204 µm), being shorter in Physopeltini (7053 µm; 6713 µm; 5415 µm, Table 2)). In Pyrrhocoris sibiricus, the labium was much shorter (3487 µm) [17]. The mentioned species belong to two closely related families of seed-feeding bugs, so the differences in length of the labium may be regarded as taxonomic characteristics for these families.…”
Section: Mouthpart Morphologymentioning
confidence: 99%
See 3 more Smart Citations
“…There were distinct differences in total length of the labium among the four largid bug species observed (longest in Macrocheraia grandis (Lohitini: 19,204 µm), being shorter in Physopeltini (7053 µm; 6713 µm; 5415 µm, Table 2)). In Pyrrhocoris sibiricus, the labium was much shorter (3487 µm) [17]. The mentioned species belong to two closely related families of seed-feeding bugs, so the differences in length of the labium may be regarded as taxonomic characteristics for these families.…”
Section: Mouthpart Morphologymentioning
confidence: 99%
“…The latter are formed by the mandibles and the maxillae, which are entirely or partly covered by the sheath. Previous studies of hemipteran mouthparts have shown that these structures differ among taxa [8,[12][13][14][15][16][17], reflecting adaptations to different diets and the fact that the specialized digestive system has contributed to their success in feeding on a broad range of foods [18]. Previous studies have focused on Pentatomomorpha species of economic importance [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, it is the way of feeding, rather than the specific diet or prey, that determines the shape of mandibles as well as other units of a mouthpart (Samways et al, ). Although detailed investigations of the mouthparts allow conclusions about feeding preference (Jiang & Hua, ; Krenn, Fournel, Bauder, & Hugel, ; Wang & Dai, ), it is only of limited value, and further behavioral investigations, as well as detailed analysis on gut content are necessary to study the specific feeding behavior of lady beetles.…”
Section: Discussionmentioning
confidence: 99%